A Critical Discourse Analysis of “Somebody’s Pleasure” By Aziz Hedra Using Teun A. Van Dijk’s - Mida Lestari; Sania Syarifatul Fadilah; Anggun Almahera (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This article explores the song lyrics of “Somebody’s Pleasure” by Indonesian artist Aziz Hedra through the lens of Teun A. van Dijk’s Critical Discourse Analysis (CDA). The song reveals a narrative of emotional neglect, objectification, and the yearning for genuine affection. Van Dijk’s three-dimensional model—textual structure, cognitive processes, and social context—is applied to dissect how the language in the song reflects individual mental states and broader social ideologies regarding love, self-worth, and power relations in modern relationships.